Multilingualism in Kemujan, Karimunjawa, Indonesia - Deli Nirmala (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
Karimunjawa can be studied not only from social aspect but also from multilingualism. This paper aims at investigating the languages living in Karimunjawa and their vitality. The study is focused on Kemujan island whose languages are Javanese, Buginese, Maduranese, Mandarese, and bahasa Indonesia. To see the vitality of them, I used UNESCO check list, observation, and interview. Referential and distributional methods were used to show how languages were used, language contact, and language vitality. The result indicates that bahasa Indonesia is the first dominant, Javanese is the second dominant, Buginese is the third, Maduranese is the fourth, and Mandarese is the least dominant.